‘Foreigners’, ‘ethnic minorities’, and ‘non-Western allochtoons’: an analysis of the development of ‘ethnicity’ in health policy in the Netherlands from 1970 to 2015 - Helberg-Proctor, Alana (BMC Public Health, 2017)
BACKGROUND: The Netherlands, because of the sustained and systematic attention it paid to migrant and minority health issues during the last quarter of the twentieth century, has been depicted as being progressive in its approach to healthcare for migrants and minorities. Recently, however, these progressive policies have changed, reflecting a trend towards problematising issues of integration in order to focus on the responsibilities that migrants and ethnic minorities bear in terms of their health. This article explores these shifts and specifically the development of particular categories of ethnicity, and examines the wider consequences that have arisen as a result. METHODS: The analysis presented here entailed a qualitative content analysis of health policies for migrants and ethnic minorities from 1970 to 2015, and examined various documents and materials produced by the institutions and organisations responsible for implementing these healthcare policies during the period from 1970 to 2015. RESULTS: Four distinct periods of political discourse related to health policy for migrants and ethnic minorities were identified. These periods of political discourse were found to shape the manner in which ethnicity and various categories and representation of foreigners, later ethnic minorities, and at present non-Western allochtoons are constructed in health policy and the implantation practices that follow. At present, in the Netherlands the term allochtoon is used to describe people who are considered of foreign heritage, and its antonym autochtoon is used for those who are considered native to the Netherlands. We discuss the scientific reproduction and even geneticisation of these politically produced categories of autochtoon, Western allochtoon, and non-Western allochtoon—a phenomenon that occurs when politically produced categories are prescribed or taken up by other health sectors. CONCLUSIONS: The categories of autochtoon, Western allochtoon, and non-Western allochtoon in the health sciences and the field of ethnicity and health in the Netherlands today have been co-produced by society and science. Policy formulated on the basis of specific political discourse informs the conceptualisations about groups and categories, issues, and solutions, and when these are institutionalised in subsequent health policy, databases, research, and care practices, these ethnic categorisations are replicated in a manner that renders them ‘real’ and enables them to be applied both socially and scientifically, culminating in pronouncements as to who is the same and who is different in Dutch society and science.